Pendampingan Pengelolaan Sampah Organik pada Masyarakat Desa Gerbo Pasuruan - Zuhriyah, Aminatuz; Mauludy Sastra, Adam; Ainul, Ainul; Wulandari, Wulandari (LP2M INSURI Ponorogo, 2022)
Waste disposal and management is the biggest threat to the environment and the people of Kejoren hamlet, Gerbo village. This service is carried out to start a program for handling waste problems, especially wet waste, starting from the beginning until it becomes clean waste that is utilized as much as possible. The service team uses the Participatory Action Research (PAR) method with a SWOT analysis strategy to describe the events that arise according to the circumstances in the village concerned. The results of the dedication through distributing questionnaires carried out pre-activity, and post-activity explained that the community's response and knowledge about waste management had increased.